Electives in Zimbabwean High Schools: Examining Attributes which Influence Prospective Students for Physical Education and Home Economics in Masvingo - Mudekunye, Jenet; Mpofu , Molyn; Manwa, Lokadhia (International Journal of Advance Research in Education & Literature (ISSN 2208-2441), 2020)
This interpretive inquiry sought to establish the attributes which influence prospective students for electives such as Home Economics (HE) and Physical Education (PE) in Zimbabwean High Schools. The study employed a qualitative descriptive survey to solicit data on choice of electives from a pollution of about four hundred students. A sample of forty (40) students was randomly selected from the four (4) schools in the district. In-depth interviews and focus group discussions were the tools used to collect data. The findings from this study revealed that high school students faced numerous challenges which were related to factors such as failure of the government, parents and the community to adequately fund electives (HE and PE). Hence, resource provision/ sponsorship of the practical subjects discouraged students from selecting the subjects. The findings also revealed that the selection process of electives in Zimbabwean high schools leaves a lot to be desired in that it is stressful and confusing. This study recommends that policies regarding subject grouping and student selection of subjects be revisited by the government after wide consultation with all the stake holders in order to reduce the flaws of the current one. Resource provision and sponsorship for electives need to be greatly improved as a means to attract subject takers for electives.